Relevansi Mahasiswa Iain Palangkaraya Terhadap Keseimbangan Hak Dan Kewajiban Warga Negara Dalam Membangun Masyarakat Berkeadilan - Florence Angelaila Fauzi; Zumiyati Zumiyati; Ulpia Rahim; Ikrimah Ikrimah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
In the context of globalization and evolving social change, the role of students in creating a balance of rights and obligations of citizens and building a just society is becoming increasingly important. This study uses a qualitative method with a questionnaire as a data collection tool to explore students' views and practices related to their rights and obligations as citizens. Through the analysis of data obtained from respondents, this study aims to identify factors that influence the role of university students in creating a just and equitable society. The results show that students have great potential as agents of change in society. With their higher education and knowledge, students are able to influence positive changes in achieving a balance of rights and obligations of citizens. Students' active participation through social movements, advocacy activities, and civic education in higher education can help create a more just and equitable society. This research is expected to provide in-depth insight into how students can effectively become agents of change in building a more just and equitable society.